Long-range DNase I hypersensitivity mapping reveals the imprinted Igf2r and Air promoters share cis-regulatory elements - Pauler, Florian M.; Stricker, Stefan H.; Warczok, Katarzyna E.; Barlow, Denise P. (Genome Research, 2005)
Epigenetic mechanisms restrict the expression of imprinted genes to one parental allele in diploid cells. At the Igf2r/Air imprinted cluster on mouse chromosome 17, paternal-specific expression of the Air noncoding RNA has been shown to silence three genes in cis: Igf2r, Slc22a2, and Slc22a3. By an unbiased mapping of DNase I hypersensitive sites (DHS) in a 192-kb region flanking Igf2r and Air, we identified 21 DHS, of which nine mapped to evolutionarily conserved sequences. Based on the hypothesis that silencing effects of Air would be directed towards cis regulatory elements used to activate genes, DHS are potential key players in the control of imprinted expression. However, in this 192-kb region only the two DHS mapping to the Igf2r and Air promoters show parental specificity. The remaining 19 DHS were present on both parental alleles and, thus, have the potential to activate Igf2r on the maternal allele and Air on the paternal allele. The possibility that the Igf2r and Air promoters share the same cis-acting regulatory elements, albeit on opposite parental chromosomes, was supported by the similar expression profiles of Igf2r and Air in vivo. These results refine our understanding of the onset of imprinted silencing at this cluster and indicate the Air noncoding RNA may specifically target silencing to the Igf2r promoter.
10.1101/gr.3783805